KEWENANGAN PENYELESAIAN SENGKETA KONSUMEN LEMBAGA PEMBIAYAAN ANTARA BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DENGAN LEMBAGA ALTERNATIF PENYELESAIAN SENGKETA (LAPS) - Titia Tauhiddah; Busyra Azheri; Yussy Mannas (Universitas Muhammadiyah Sumatera Utara, 2020)
One of the government's efforts to resolve consumer disputes through non-litigation is through the Consumer Dispute Resolution Agency (BPSK). In addition, the Financial Services Authority (OJK) also mandates the establishment of institutions to resolve financial service sector consumer disputes, namely the Alternative Consumer Dispute Resolution Institute (LAPS). The study was conducted normatively. The study emphasizes the authority to resolve consumer disputes at financial institutions between BPSK and LAPS. The results show that BPSK has the authority to settle final consumer disputes, the authority exercised by BPSK is regulated in the Decree of the Minister of Industry and Trade of the Republic of Indonesia Number: 350 / MPP / Kep / 12/2001 concerning the Implementation of the Duties and Authorities of the Consumer Dispute Resolution Board and the Republic of Indonesia's Minister of Trade Regulation Indonesia Number 06 / M-DAG / PER / 2/2017 concerning the Consumer Dispute Resolution Board. It's just that the decisions issued by BPSK related to the case of financial institutions, especially those containing elements of the credit agreement are often canceled by the Supreme Court because BPSK considered not authorized to settle disputes that contained the agreement element. The authority of LAPS is regulated in POJK Number 1 / POJK.07 / 2014 concerning Alternative Institutions for Settlement of Financial Services Sector Disputes. LAPS divides financial services sector dispute resolution institutions into 6 institutions, the establishment of which is carried out by the OJK in collaboration with Financial Services Institutions. LAPS which has the authority to settle consumer financing company disputes is BMPPVI (Indonesian Ventura Medication, Financing, And Capital Mediation Agency).